Answer:
g(x)=3
Step-by-step explanation:
Let's find the answer.
W(f,g)=3e^x which can be written as:
W(f,g)=(3)*(e^x), notice that:
(e^x)=f(x) so:
W(f,g)=3*f(x), establishing:
W(f,g)=g(x)*f(x) then:
g(x)=3
In conclusion, g(x)=3.
By changing their exponent to negative.
Ex.
9514 1404 393
Answer:
Step-by-step explanation:
The marked angles are supplementary, so ...
(5x +26)° +(8x -2)° = 180°
13x = 156 . . . . . . . . . . . . . . divide by °, subtract 24
x = 12 . . . . . . . . . . . divide by 13
∠H = (8x -2)° = (8·12 -2)°
∠H = 94°
Answer:
See below.
Step-by-step explanation:
It would take a long time to explain . There is a good method called Newton's method which involves graphs of the type
y = x^3 - n and applying calculus to produce cycles of approximation until you'll get close to the required cubic root.
You'll find it on online videos.
Answer:
$600,000:$800,000
Step-by-step explanation: